The Joint Development of Hemispheric Lateralization for Words and Faces. - Dundas, Eva M.; Plaut, David C.; Behrmann, Marlene (Journal of Experimental Psychology. General, 2013)
Consistent with long-standing findings from behavioral studies, neuroimaging investigations have identified a region of the inferior temporal cortex that, in adults, shows greater face selectivity in the right than left hemisphere and, conversely, a region that shows greater word selectivity in the left than right hemisphere. What has not been determined is how this pattern of mature hemispheric specialization emerges over the course of development. The present study examines the hemispheric superiority for faces and words in children, young adolescents and adults in a discrimination task in which stimuli are presented briefly in either hemifield. Whereas adults showed the expected left and right visual field superiority for face and word discrimination, respectively, the young adolescents demonstrated only the right-field superiority for words and no field superiority for faces. Although the children's overall accuracy was lower than that of the older groups, like the young adolescents, they exhibited a right visual field superiority for words but no field superiority for faces. Interestingly, the emergence of face lateralization was correlated with reading competence, measured on an independent standardized test, after regressing out age, quantitative reasoning scores, and face discrimination accuracy. Taken together, these findings suggest that the hemispheric organization of face and word recognition do not develop independently and that word lateralization, which emerges earlier, may drive later face lateralization. A theoretical account in which competition for visual representations unfolds over the course of develop-ment is proposed to account for the findings.